2011
DOI: 10.1016/j.ijpvp.2011.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Shakedown and limit analysis of 90° pipe bends under internal pressure, cyclic in-plane bending and cyclic thermal loading

Abstract: The Linear Matching Method is used to create the shakedown limit and limit load interaction curves of 90 degree pipe bends for a range of bend factors. Two load cases are considered i) internal pressure and in-plane bending (which includes opening, closing and reversed bending) and ii) internal pressure and a cyclic through wall temperature difference giving rise to thermal stresses.The effects of the ratios of bend radius to pipe mean radius (R/r) and mean radius to wall thickness (r/t) on the limit load and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 12 publications
1
18
0
1
Order By: Relevance
“…A long rod of length, equal to five times the bend radius (R) was attached at the free end for applying the in-plane load. Spring balance and load cell were used to measure the magnitude of the applying load which is placed at the free end of the rod [10]. Dial gauges were used to measure the deflection in the bend section by fixing it in the intrados, crown and extrados regions (Fig.…”
Section: Experimental Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…A long rod of length, equal to five times the bend radius (R) was attached at the free end for applying the in-plane load. Spring balance and load cell were used to measure the magnitude of the applying load which is placed at the free end of the rod [10]. Dial gauges were used to measure the deflection in the bend section by fixing it in the intrados, crown and extrados regions (Fig.…”
Section: Experimental Evaluationmentioning
confidence: 99%
“…Besides shape irregularities, pipe diameter, wall thickness and bend radius also effect a change in stress in bend region [4]. However, the majority of the existing solutions have been developed either empirically based on test data or analytically based on a simple equilibrium stress field and yield criterion considering without the effect of ovality in pipe bends [5][6][7][8][9][10], thus the resulting solutions tend to under predict the actual limit loads, which lead to failure in bend region. Effect of ovality in pipe bend should be quantified and included in limit loads solution to avoid failure.…”
Section: Introductionmentioning
confidence: 99%
“…Iterative elastic technique is a typical approach which contains Elastic Compensation Method [4], GLOSS R-node method [5], LMM [6], and so on. The LMM has acquired distinguished reputation of providing accurate result for many complicated geometries subjected to complex loading as well as it can consider temperature dependent material parameters [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Upon comparison with ASME B31.3 and EN 13480-3 design standards for occasional loading conditions, Varelis et al[11] results highlighted lack of design provisions within the low cycle fatigue range. Chen H. et al[12] generated SD domains utilizing the Linear Matching Method (LMM) for sound pressurized elbows subjected to cyclic IPO, IPC, and reversed bending modes. Cyclic through wall temperature difference of pressurized elbows was also studied to investigate the effect of thermal stresses on generated SD domains.…”
mentioning
confidence: 99%
“…Cyclic through wall temperature difference of pressurized elbows was also studied to investigate the effect of thermal stresses on generated SD domains. It is reported that application of cyclic thermal load resulted in significant reduction in SD domains[12]. Wood et al[13] conducted experimental tests and FE analyses on 90 degree sound pressurized single unreinforced mitred bend subjected to cyclic IPC bending.…”
mentioning
confidence: 99%